ANALYSIS OF SOCIOECONOMICS AND FEED EFFICIENCY OF CATFISH PRODUCTION IN OYO STATE, NIGERIA - AJAGBE, S. O.; AJAGBE, R. O.; ABDULAZEEZ, F. I.; OJUBOLAMO, M. T.; OLOMOLA , A. O.; OKE, O. S.; GANIYU, O. A.; AKINWALE, G. T.; OYEKAN , O. O.; ADEKANMBI, T. O. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2022)
Catfish farming is capital intensive, and its profitability depends on efficient combination and utilization of input variables. This study examines the socioeconomic characteristics of small-scale catfish farmers as well as the contribution of various input resources to catfish production and catfish feed efficiency. Structured questionnaire was used to collect data from 200 catfish farmers in four randomly selected local government areas of Oyo State, Nigeria. Descriptive statistics and economics ratios were used to analyze the collected data. This result showed that the ages of catfish farmers vary between 27 and 72 years with a mean of 41±1.65 years old. Majority (74.5%) of catfish farmers were male while 25.5% were female. Most (63.0%) catfish farmers are married. Most (67.5%) catfish farmers have household size that varied between 5 and 8. The survival percentage of catfish in the study areas varies between 73.3% and 97.5% with a mean of 87.88 ± 0.93%. Feed is the single largest contributing input variable in catfish production. There is no conventional method of feeding fish. The mean feed conversion ratio (FCR) was 1.42±0.12. The gross yield varied between 0.04 g/ft2 and 3.49 g/ft2 with a mean of 0.93 ± 0.08 g/ft2. Likewise, the growth rate of catfish varied between 4.10 (g/day) and 14.83 (g/day) with a mean of 7.68 ± 0.29 (g/day).  Therefore, farmers should know that the lower the FCR, the lower cost of production and the higher the profit.